АХБОРАТЛАШУВ ЖАРАЁНЛАРИНИНГ ЖАМИЯТ ТУЗИЛИШИДА КЕЛТИРИБ ЧИҚАРАЁТГАН ЎЗГАРИШЛАРИ: ИСТИҚБОЛДАГИ ИМКОНИЯТЛАР ВА МУАММОЛАР - Ескараев, Т. (SCIENCE and SOCIETY, 2021)
The article is analysed some views about further changes in the system of society due to the development of information technologies. They are considered notion information society, virtualization of the economy, informatization for the development society.